Imagining interceptions: Eye movements as an online indicator of covert motor processes during motor imagery - D’Aquino, Alessio; Frank, Cornelia; Hagan, John Elvis; Schack, Thomas (Frontiers in Neuroscience, 2022)
The analysis of eye movements during motor imagery has been used to understand the influence of covert motor processes on visual-perceptual activity. There is evidence showing that gaze metrics seem to be affected by motor planning often dependent on the spatial and temporal characteristics of a task. However, previous research has focused on simulated actions toward static targets with limited empirical evidence of how eye movements change in more dynamic environments. The study examined the characteristics of eye movements during motor imagery for an interception task. Twenty-four participants were asked to track a moving target over a computer display and either mentally simulate an interception or rest. The results showed that smooth pursuit variables, such as duration and gain, where lower during motor imagery when compared to passive observation. These findings indicate that motor plans integrate visual-perceptual information based on task demands and that eye movements during imagery reflect such constraint.